Proceedings of the 13th EAI International Conference on Pervasive Computing Technologies for Healthcare - Demos and Posters 2019
DOI: 10.4108/eai.20-5-2019.2283493
|View full text |Cite
|
Sign up to set email alerts
|

Design of an Ontology for Decision Support in VR Exposure Therapy

Abstract: Virtual Reality (VR) is finding its way into many domains, including healthcare. Therapists greatly benefit from having any scenario in VR at their disposal for exposure therapy. However, adapting the VR environment to the needs of the patient is time-consuming. Therefore, an intelligent decision support system that takes context information into account would be a big improvement for personalised VR therapy. In this paper, a semantic ontology is presented for modelling relevant concepts and relations in the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…This was achieved by using the ontology to represent users' health conditions, domestic situations, and a variety of comfort indicators, thereby enabling the personalisation of the services provided to specific target users. Another study reported the significance of incorporating an ontology for medical decision support (Heyse et al, 2019 ). In this study, the authors designed an ontology for VR Exposure Therapy to enable a better service to the target patients and help improve relevant decision support systems.…”
Section: Related Workmentioning
confidence: 99%
“…This was achieved by using the ontology to represent users' health conditions, domestic situations, and a variety of comfort indicators, thereby enabling the personalisation of the services provided to specific target users. Another study reported the significance of incorporating an ontology for medical decision support (Heyse et al, 2019 ). In this study, the authors designed an ontology for VR Exposure Therapy to enable a better service to the target patients and help improve relevant decision support systems.…”
Section: Related Workmentioning
confidence: 99%
“…Therefore, to have the lens of DSR into ontology design is a fruitful idea. 61,71,72 As a result, Ahmad et al 57 recommended a new methodology that can be flexible and generic. In the method, ontology development methodology is rooted in DSRM according to DSRM's design and development, demonstration, evaluation, and communication activities.…”
Section: Conclusion and Recommendationmentioning
confidence: 99%
“…The ontology based system was evaluated using a within-subject experiment in order to confirm the performance of the ontology in helping patients to recollect their lost memories. www.ijacsa.thesai.org 3) Ontology for VR exposure therapy (VRET): In this project [17], semantic ontology was designed with the purpose to model the necessary knowledge (e.g., concepts and relation) in a way to represent the domain of anxiety therapy in VE. The aim of the designed ontology was also to provide semantic reasoning in order to deduce essential knowledge from low-level data in VRET.…”
Section: A the Designed Ontologies In Different Domainsmentioning
confidence: 99%